EFFECT OF ARBUSCULAR MYCORRHIZA FUNGI INOCULATION ON TEAK (Tectona grandis Linn. F) AT CIKAMPEK, WEST JAVA - Irianto, Ragil S.B.; Santoso, Erdy (Secretariat of Forestry Research and Development Agency, 2005)
The aim of this study was to identify the effect of Arbuscular Mycorhiza Fungi (AMF) on the early growth of teak (Tectona grandis Linn. F) plantation. Teak seedlings were inoculated with Glomus aggregatum or Mycofer (mixing of four Arbuscular Mycorrhiza Fungi (AMF) : G. margarita, G. manihotis, G. etunicatum and Acalospora spinosa) at the time of transplantation. AtÂ three months old the seedlings were planted in Cikampek experimental forest. Results showed that application of G. aggregatum or mycofer to teak could accelerate height and diameter growth by up to 61%and4 7%, respectively, after three months in the field.